KNOWLEDGE MANAGEMENT ASSESSMENT AS FOUNDATION IN IMPROVING ORGANIZATION COMPETITIVENESS: CASE STUDY AT IT SERVICE & CONSULTANCY COMPANY - MAULINA (NIM 29316028), SYELLA
PT Sapphire System (PT SS) is a foreign capital investment company which located in Jakarta area. PT SS business is in IT sector as an IT services and consultancy with business to business scheme. Currently, PT SS face a low customer satisfaction which caused by new employee that considered by customer to have limited skill compared with current active consultant as well as high turnover. The problem in PT SS is directly linked on how PT SS managed the knowledge in the company, thus a knowledge management maturity assessment is conducted to understand the level of knowledge management PT SS currently practice. The assessment was conducted using tools from Asian Productivity Organization (APO) which measures 7 categories that is linked with knowledge management. The result of the assessment will be used to identify the gap in PT SS knowledge management practice thus strengthen the knowledge management in PT SS. The assessment is limited only to division who provides services to customer with additional human resource and quality control division that managed the overall KM activity. The assessment result shows that PT SS has implemented knowledge management practices in terms of process especially documentation of procedures and work process, yet the gap still found in terms of motivation for knowledge sharing and collaboration activity. Based on this result an improvement plan is proposed to strengthen the governance of knowledge management and ensuring the empowerment of knowledge management activity in PT SS to motivate employee and ensure the knowledge sharing activity. To improve the knowledge management practices, empowerment should start from the company strategic plan and involvement of PT SS management to promote knowledge management practices. HR should collaborate with Division Head to assign knowledge management role and responsibilities to PT SS employee and the implementation of the practices will be reviewed by quality control division. The activity of knowledge sharing and collaboration should also be monitored by company and acknowledged by include the achievement of those activities in performance review. The change of company culture and several chances to improve knowledge for millennial generation should also be considered such as scholarship and chances to work at the Headquarter. Additionally, improvement in terms of implementation of suitable technology to further motivate knowledge sharing and collaboration activity should be executed.